2008
DOI: 10.1007/s11307-008-0142-7
|View full text |Cite
|
Sign up to set email alerts
|

Direct Site-Specific Radiolabeling of an Affibody Protein with 4-[18F]Fluorobenzaldehyde via Oxime Chemistry

Abstract: Purpose-In this study, we introduce a methodology for preparing 18 F-labeled Affibody protein, specifically 18 F-Anti-HER2 dimeric Affibody (14 kDa), for in vivo imaging of HER2neu with positron emission tomography (PET). Conclusion-Site-specific 18 F-labeled Affibody against HER2 has been synthesized via chemoselective oxime formation between an aminooxy-functionalized Affibody and 18 Ffluorobenzaldehyde. The results have implications for radiolabeling of other affibodies and macromolecules and should also be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 17 publications
(26 reference statements)
2
54
0
Order By: Relevance
“…Unlike Affibody molecules labeled using residualizing radiometal labels 22,23,32,35 , the renal retention of 18 F-N-(4-fluorobenzylidine)oxime-labeled Affibody molecules is quite low (Figure 9). This is in agreement with data showing rapid clearance of radioactivity from kidneys for other Affibody molecules labeled with 18 F-N-(4-fluorobenzylidine)oxime 19,29,30 . This is a strong indication that the Experiments in tumor-bearing mice confirmed that 18 F-FBO-E 3 -PEP4313 can target HER2-expressing xenografts with high specificity (Figure 8).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Unlike Affibody molecules labeled using residualizing radiometal labels 22,23,32,35 , the renal retention of 18 F-N-(4-fluorobenzylidine)oxime-labeled Affibody molecules is quite low (Figure 9). This is in agreement with data showing rapid clearance of radioactivity from kidneys for other Affibody molecules labeled with 18 F-N-(4-fluorobenzylidine)oxime 19,29,30 . This is a strong indication that the Experiments in tumor-bearing mice confirmed that 18 F-FBO-E 3 -PEP4313 can target HER2-expressing xenografts with high specificity (Figure 8).…”
Section: Discussionsupporting
confidence: 92%
“…In fact, 18 F-fluorobenzaldehyde conjugation has been used for labeling of recombinant dimeric 19 and monomeric 29 anti-HER2 Affibody molecules (after conjugation of 2-…”
Section: Introductionmentioning
confidence: 99%
“…As Affibody molecules are devoid of cysteines, they allow homogenous site-specific labeling using maleimide chemistry after the introduction of a single cysteine for such labeling purposes. [35][36][37][38] Here we report the development of PDGFRβ-specific Affibody molecules aimed for in vivo tumor targeting. Development was performed in two steps-starting with selection of binders from a naive library of Affibody molecules, followed by an affinity maturation procedure.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to [ 18 F]fluciclatide, a number of other peptides have been conjugated with [ 18 F]FBA [34,37,[41][42][43]. In general, the conjugations require low pH (e.g., pH 2.5 or below) and heating (60-70 8C) to improve reaction efficiency.…”
Section: -[ 18 F]fluorobenzaldehyde ([ 18 F]fba)mentioning
confidence: 99%